2021
DOI: 10.1038/s41598-021-88292-7
|View full text |Cite
|
Sign up to set email alerts
|

Vibratory behaviour produces different vibration patterns in presence of reproductives in a subterranean termite species

Abstract: Vibratory behaviours are widespread in social insects, but the produced vibrations remain poorly explored. Communication using vibrations is an efficient way to transmit information in subterranean environments where visual and odorant signals are less efficient. In termites, different vibratory behaviours are performed in different contexts like reproductive regulation and alarm signalling, but only few studies explored the structure of the produced vibrations (i.e., duration, number of pulses, amplitude). He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 65 publications
(93 reference statements)
1
7
0
Order By: Relevance
“…Workers display more body-shaking in presence of live reproductives and extracts of reproductives than in presence of workers' extracts. In the termite R. flavipes, this behavior is a proximate of the presence of reproductives 18 , 43 , 44 (also shown in this study). Thus, we bring behavioral evidence that reproductives recognition is mediated by cuticular polar compounds, with proteins and peptides good candidates as active compounds.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Workers display more body-shaking in presence of live reproductives and extracts of reproductives than in presence of workers' extracts. In the termite R. flavipes, this behavior is a proximate of the presence of reproductives 18 , 43 , 44 (also shown in this study). Thus, we bring behavioral evidence that reproductives recognition is mediated by cuticular polar compounds, with proteins and peptides good candidates as active compounds.…”
Section: Discussionsupporting
confidence: 82%
“…For this purpose, we used aqueous extraction of polar compounds for both protein profiling and for behavioral assays. It has been previously demonstrated that body-shaking of workers (a vibratory behavior) was involved in reproductives recognition in the termite R. flavipes , since workers expressed this vibratory behavior in presence of reproductives or eggs 18 , 43 , 44 . Here we show that cuticular polar extracts from reproductives contain compounds that have the ability to trigger body-shaking, while extracts from workers do not.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They represent an effective form of communication in termites, especially in subterranean environments where visual and odorant signals can be less effective (Hill, 2009). Termites are therefore able to transmit different signals using shaking behavior, such as alarm signaling, caste identification and reproductive regulation (Eyer et al, 2021;Pailler et al, 2021). In addition, termites can exhibit different behaviors toward infected nestmates.…”
Section: Introductionmentioning
confidence: 99%